Geschlossen, lang oder gespannt? Die Beschreibung der Artikulation niederländischer Vokale aus einer polykonfrontativen (und didaktischen) Perspektive - Zuzanna Czerwonka-Wajda (Linguistische Treffen in Wrocław)
By analyzing the descriptions of Dutch vowels in the selected literature in four languages (Dutch, Polish, German and English), this paper addresses issues at the intersection of terminology and phonetics, while also placing them in the context of comparative research to provide a new broader perspective. The starting point are the articulatory features of vowels based on which the course of vocalic articulation is later described separately for every language. Material for the analysis comes from two sources per language. In the first part of the analysis, a question about the (lack of) quality of terminology used in the material is being answered, followed by indicating different interpretive traditions of vowel description in the given language, which are e.g. expressed by the use of terms such as “closed”, “lang” and “gespannt”. The second part of the analysis uses the multilingual nature of the corpus to provide a polyconfrontative view of the problem. It is being shown that the terms used in the descriptions in the four chosen languages are hardly international in nature which makes finding equivalents quite difficult. This lack of equivalence in the descriptions not only makes the language comparison harder but also impacts the didactics of pronunciation, as students of Dutch have to re-learn terminology in this language even if they learned it in Polish, English or German.